A new method for the detection of phospholipase A2 variants: Identification of isozymes in the venoms of newborn and adult Bothrops asper (terciopelo) snakes - Moreno, Edgardo (1988)
E. Moreno, A. Alape, M. Sánchez and J. M. Gutiérrez. A new method for the detection of phospholipase A2 variants: identification of isozymes in the venoms of newborn and adult Bothrops asper (terciopelo) snakes. Toxicon 26, 363 - 371, 1988. - A new method for the identification of phospholipase A2 isozymes in snake venoms is described. The technique is based on the separation of the venom components by isoelectric focusing in agarose gels, transfer of the protein bands by diffusion onto nitrocellulose paper and detection of the phospholipolytic activity of the enzymes by a hemolytic assay either in agarose gels or by benzidine reaction on a solid matrix. Striking differences in the electrophoretic patterns of the phospholipase A2 isozymes between the Atlantic and Pacific venoms and between the newborn and adult venoms from Bothrops asper specimens were observed. The method allowed the detection of 9 different phospholipase A2 isozymes in the venom of adult Atlantic, 7 isozymes in the venom of adult Pacific, and 2 - 3 isozymes in the venoms of newborn specimens. Horse polyvalent antivenom varied in its capacity to neutralize the phospholipolytic activity of the different isozymes in the same venom and among different venoms.